Employment and labour hoarding: a production function approach - Vella, Melchior (2018)
Purpose – This paper aims to test the hypothesis that the effect of production slowdown on labour demand can be muted by labour hoarding. Design/methodology/approach – This study adopts a production function approach, using data from Malta, a small state in the EU. Findings – The results confirm the hypothesis and indicate that firms are normally prepared to employ and dismiss more workers in the long run than in the short run. Practical implications – This finding has important implications for developed countries, including that labour hoarding can be of certain relevance in times of economic slowdown as shocks are absorbed by internal flexibility. Originality/value – The results of this study add on to the existing literature in two ways. First, this study compares two industries–manufacturing and financial services–for which the former sector received support to hoard labour after the financial turmoil of 2008. Consequently, the dominance of labour hoarding in manufacturing relative to financial services is uncovered and the effect of hoarding practices on labour demand is estimated. Second, Malta is an interesting case because it is one of the smallest economies in the world and faces a high degree of vulnerability because of constraints associated with small size and insularity. As a result,firms adopt policy-induced measures to minimise adjustment costs.